Complexes Formation of Some Bivalent Metal Ions with Oxygen Sulphur Donor Ligands - Basak*, Devashish (Asian Journal of Chemistry, 2010)
Complexation reactions of thiomalic acid (TMA), thiolactic acid (TLA) and thioglycolic acid (TGA) with Mn(II), Ni(II), Co(II), Cu(II) and Zn(II) have been studied in solution phase using the technique of paper electrophoresis at a fixed ionic strength μ = 0.1 M (HClO4) at 25 ± 1ºC and their stability constants have been reported. The values are in good agreement with the Irving and Williams series.